2021
DOI: 10.1186/s12263-021-00683-7
|View full text |Cite
|
Sign up to set email alerts
|

Consumer acceptance of genetic-based personalized nutrition in Hungary

Abstract: Background Despite the increasing number of personalized nutrition services available on the market, nutrigenomics-based level of personalization is still the exception rather than a mainstream activity. This can be partly explained by various factors of consumer acceptance of the new technology. While consumer attitudes toward genetic tests aiming to reveal the risks of a predisposition to various illnesses have already been examined by several research studies worldwide; consumer acceptance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
10
0
3
Order By: Relevance
“…The results imply that males may be less receptive to personalised nutrition and less likely to take it up in the future. The finding that males held less favourable attitudes and were less likely than females to intend to adopt personalised nutrition agrees with previous survey research on healthy eating (Hiller et al 2017) and on personalised nutrition (Szakaly et al 2021;Stewart-Knox et al 2009). This, along with results from the wider Food4Me survey (Fischer et al 2016) indicating that males were less willing to pay for personalised nutrition than females, implies that personalised, nutritional genomic intervention should target men and women differently (Corella et al 2019).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results imply that males may be less receptive to personalised nutrition and less likely to take it up in the future. The finding that males held less favourable attitudes and were less likely than females to intend to adopt personalised nutrition agrees with previous survey research on healthy eating (Hiller et al 2017) and on personalised nutrition (Szakaly et al 2021;Stewart-Knox et al 2009). This, along with results from the wider Food4Me survey (Fischer et al 2016) indicating that males were less willing to pay for personalised nutrition than females, implies that personalised, nutritional genomic intervention should target men and women differently (Corella et al 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Studies on attitudes and adoption of personalised nutrition in relation to sociodemographic factors, however, are scarce. Surveys conducted in Hungary ( N = 1000) (Szakaly et al 2021 ), ( N = 500) (Szakaly et al 2016 ) and another in six EU countries ( N = 5967) (Stewart-Knox et al 2009 ) both suggested that attitudes toward personalised nutrition were more favourable in women than men. The Hungarian survey (Szakaly et al 2016 ) also identified more favourable attitudes among those with a higher education level.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of several articles directly relevant to the dietetics community from around the world revealed that these articles continue to use the term nutrigenomics to describe the use of genetic variations to personalize dietary recommendations. [2][3][4][5][6][7][8][9][10][11][12] The use of the term nutrigenomics is similarly used by various regulatory bodies and dietetic organizations globally. [13][14][15][16][17] Importantly, to avoid potential confusion, we indicated in the introduction of the article that "the term nutrigenomics is used to describe the application of genetic information to personalize nutrition recommendations."…”
Section: Authors' Responsementioning
confidence: 99%
“…GPN is important to social marketing as the uptake of individual "roadmaps" of diet, nutrition and exercise set GPN apart from health "fads" that may not change health behaviour (Celis-Morales et al, 2017;Chaudhary et al, 2021). As genomic science is at the forefront of social change in medicine, biotechnology and bioengineering (Galimberti et al, 2019), so too may the unique health programmes of GPN facilitate social change in marketing (Szak aly et al, 2021). In this vein, GPN may be recognised as an empowerment tool to promote health behaviour in consumers (Besson et al, 2020), delivering on broad social change (Carvalho and Mazzon, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, although GPN is becoming increasingly important in social health research (Fenech, 2019), GPN programmes remain a niche activity and are not yet mainstream among consumers (Szak aly et al, 2021). Further, the lion's share of marketing research has explored consumer acceptance of GPN (Poínhos et al, 2018;Kiss, 2019;Stewart-Knox et al, 2019;Reinders et al, 2020), whereas research on how consumers engage with GPN programmes remains limited (Rusu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%